Music is red : the politicisation of music in China, 1919–1989 - Pang, Metha Hui Shan (Nanyang Technological University, 2022)
Given the Westernisation of Chinese music that can be clearly heard today, this thesis examines the changes and continuities in music practices that can be observed in China, more specifically the People’s Republic of China, from 1919–1989. Music is used as a powerful tool to win the hearts and minds of the people. Popular culture, in the form of various mediums such as art, literature, films, posters and music, could be used as a form of soft propaganda that could effectively shape the opinion of the domestic public. Music has the power to convey emotions and messages in recognisable ways, and this power was definitely recognised by the people of China. This paper finds that in order to harness this power, the evolution of music in China has become highly politicised. This is not only apparent in the content and rhythm of the song, but in the way the masses also interact with music perpetuated by the government. While the ruling government at the time might have specific censorship policies or restrictions, the masses will eventually find a way to be heard.